Characteristics of unvaccinated and vaccinated critically ill COVID-19 patients in calabria region (Italy): A retrospective study - Bruni, Andrea; Longhini, Federico; Macheda, Sebastiano; Biamonte, Eugenio; Pasqua, Pino; Neri, Giuseppe; Guzzo, Maria Laura; Garofalo, Eugenio, Calabria COVID-ICU Network authors; Caroleo, Antonio; Chirico, Paolo; Corea, Angela; et al. (Frontiers in Medicine, 2022)
Introduction: After the rapid surge of a novel coronavirus (SARS-CoV-2) in 2020 anti-SARS-CoV-2 vaccines have been developed to prevent the development of critical forms of COVID-19 leading to Intensive Care Unit (ICU) admission. The possibility of ICU admission after the first-cycle vaccination has been already reported; however, no data have been published regarding vaccinated patients with a “booster” dose. This retrospective study describes the characteristics of critically ill patients after the implementation of the regional “booster” dose vaccination program in a southern region of Italy. Material and Methods: We screened all medical records of critically ill COVID-19 patients in the period between January to April 2022. We collected the demographic characteristics, the presence of comorbidities, the vaccination status, the clinical course (arterial blood gases and type of respiratory support) and outcomes (rate of tracheostomy, ICU length of stay and mortality). Results: A total of 272 patients were admitted to ICUs during the study period. 161 patients were unvaccinated, whereas 111 were vaccinated with the complete first-cycle or “booster” dose. The type of respiratory support was similar between groups. Vaccinated patients were characterized by a better oxygenation throughout the whole ICU length of stay. Fourteen unvaccinated and 3 vaccinated patients required tracheostomy (p=0.045). ICU length of stay was 12.2 (±7.3) days in unvaccinated patients and 10.4 (±6.7) days in vaccinated patients (p=0.036). ICU mortalities were 38.5% and 24.3% in unvaccinated and vaccinated patients, respectively (p=0.014). Conclusions: Vaccinated patients have better clinical course and outcomes as compared to the unvaccinated population.